Did Securitization of Mortgage Loans Create Moral Hazards? A Study Based on the Experience of US and Malaysia - Mohd Pilus, Fairuzana (2009)
Securitization is considered as one of the most important financial development in recent history. It offer the benefits of improving returns on capital, lowering borrowing costs, diversifying risks, increasing secondary market liquidity and increasing availability of credit for mortgage borrowers.